COGNITIVE APPROACH TO USING STYLISTIC DEVICES IN ENGLISH LITERARY DISCOURSE - Husanova Dilshoda Abduganiyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Stylistic processes in literature play a crucial role in shaping the aesthetic, emotional, and intellectual impact of literary texts. This article explores the significance of stylistic processes from a cognitive perspective, examining how language choices, narrative techniques, and linguistic devices contribute to the reader's understanding and interpretation of literary works. By employing cognitive theories of language and perception, we delve into the intricate ways in which stylistic elements engage readers' mental faculties, evoke imagery, and elicit emotional responses. Through examples drawn from various literary genres and periods, this article illustrates the diverse manifestations of stylistic processes and their profound influence on literary meaning and reception.